Investment Decisions, Financing Decisions, And Dividend Policies On Company Value with GCG As A Moderating Variable In The Automotive Subsector On The Idx For The Period 2020-2023 - Jeremy Herison Saragih; Sahala Purba; Septoni Benyamin Siahaan; Ivo Maelina Silitong (Program Studi Akuntansi Universitas Simalungun, 2025)
Price Book Value (PBV) is perception of investor about sucesss of any corporate. High and superior Price Book Value (PBV) will make share and prospect of market of corporate will brighter in future. Many factors influencing Price Book Value (PBV), including philanthropy. Philanthropy (Corporate Philanthropy) is one of the Corporate Social Responsibility items as an important element in improving the company's character. The present study is a quantitative one using an associative approach, aimed to analyze effect of philanthropy on Price Book Value (PBV) using time series data obtained from the financial statements of Primary Consumer Goods Companies listed on the IDX within 2018-2022. The population consisted of 32 primary consumer goods companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. The number of samples was of 21 x 5 years of observation period = 105 issuer data. The research data analysis used a simple linear regression analysis.x Philanthropy partially has a significant effect on Price Book Value (PBV). It is indicated by the t-value X (13,034)> t-table (1.97) and p-value (0.000) <0.05. The magnitude of the effect of philanthropy on Price Book Value (PBV) is of is 62.3%. It is recommended that primary consumer goods companies listed on the Indonesia Stock Exchange pay more attention to aspects that affect company value (PBV) so that company value (PBV) can be further increased